1994
DOI: 10.1002/eji.1830240939
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular adhesion molecules (ICAM)‐1 ICAM‐2 and ICAM‐3 function as counter‐receptors for lymphocyte function‐associated molecule 1 in human immunodeficiency virus‐mediated syncytia formation

Abstract: It has been previously demonstrated that lymphocyte function-associated molecule 1 (LFA-1) plays a major role in human immunodeficiency virus (HIV)-mediated syncytia formation. In the present study we investigated the involvement of intercellular adhesion molecule-1 (ICAM-1), ICAM-2 and ICAM-3 in the process. The ability of monoclonal antibodies (mAb) directed against ICAM-1, ICAM-2 and ICAM-3 to block syncytia was analyzed either in phytohemagglutinin (PHA)-activated lymphocytes infected in vitro with primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 40 publications
(2 reference statements)
1
28
0
Order By: Relevance
“…Hildreth and Orentas (11) were the first to show that antibodies to LFA-1 inhibited syncytium formation induced by HIV. This finding was corroborated by other investigators who showed that syncytium formation in HIV-infected cultures was blocked by antibodies to the three ICAM ligands (2). The LFA-1/ ICAM-1 interaction was also found to be important for conjugation between HIV-infected dendritic cells and CD4 ϩ T cells in the absence of any syncytium formation (20).…”
supporting
confidence: 80%
“…Hildreth and Orentas (11) were the first to show that antibodies to LFA-1 inhibited syncytium formation induced by HIV. This finding was corroborated by other investigators who showed that syncytium formation in HIV-infected cultures was blocked by antibodies to the three ICAM ligands (2). The LFA-1/ ICAM-1 interaction was also found to be important for conjugation between HIV-infected dendritic cells and CD4 ϩ T cells in the absence of any syncytium formation (20).…”
supporting
confidence: 80%
“…However, the complete inhibition of THP-1 cell adhesion by anti-ICAM-1 antibody was not achieved, suggesting other molecules, such as ICAM-2 and ICAM-3, may be involved in this adhesion event induced by gp120. There is evidence that ICAM-2 and ICAM-3, in addition to ICAM-1, can function as ligands in HIVmediated syncytia formation (Butini et al, 1994). Thus, it will be important to determine whether gp120 affects the expression of ICAM-2 and/or ICAM-3 in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, aliquots of 10 5 cocultured and unmixed PMNLs were tested by different assays for the total amount of viral nucleic acids. Then, the copy number of viral DNA, IE mRNA, and pp67 mRNA per infected PMNL was calculated by dividing the total copy number for each viral nucleic acid per 10 5 PMNLs by the number of PMNLs positive for each parameter. In addition, the number of p72-and pp65-positive PMNLs and the number of PMNLs carrying infectious virus was determined according to well-standardized procedures (see below).…”
Section: Cell Cultures and Virus Strainsmentioning
confidence: 99%